Sowing the Seeds of Seagrass Recovery Using Hessian Bags - Richard Unsworth (Frontiers in Ecology and Evolution, 2019)
Seagrass meadows are an important wetland habitat that have been degraded globally but have an important carbon storage role. In order to expand the restoration of theseproductive and biodiverse habitats methods are required that can be used for large scale habitat creation across a range of environmental conditions. The spreading of seagrassseeds has been proven to be a successful method for restoring seagrass around the world, however in places where tidal range is large such methods become limited byresultant water movements. Here we describe and test a method for deploying seagrass seeds of the species Zostera marina over large scales using a new, simple method “Bagsof Seagrass Seeds Line (BoSSLine).” This method involved planting seeds and sediment using natural fiber hessian bags deployed along strings anchored onto the seabed. Whendeployed in a suitable environment 94% of bags developed mature seagrass shoots, unfortunately one site subjected to a large storm event resulted in sediment burial ofthe bags and no seed germination. Bags were filled with 100 seeds with each leading to the development of 2.37 ± 2.41 mature shoots (206 ± 87mm in length) 10 monthsafter planting. The method was proven successful however the experiments illustrated the need to ensure habitat suitability prior to their use. Low seed success rate wascomparable to other restoration studies, however further trials are recommended to ensure ways to improve this rate. In conclusion, this study provides evidence for aneffective, simple method “Bags of Seagrass Seeds Line (BoSSLine)” for deploying seeds of the seagrass Zostera marina over large scales.